1984
DOI: 10.1002/ajh.2830170402
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of polycythemia vera with hydroxyurea

Abstract: Conventional treatment of polycythemia vera (PV) with radioactive phosphorus or alkylating agents is associated with a significant excess of acute leukemia and cancer of the gastrointestinal tract and skin. There is thus a need for a nonmutagenic agent in the treatment of this disorder. Hydroxyurea (HU) was administered to 118 patients with a loading dose of 30 mg/kg/day for 1 week, which was then reduced to 15 mg/kg/day. Initial control of the elevated hematocrit and platelet count was achieved within 12 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 6 publications
0
33
0
Order By: Relevance
“…In PV patients treated with HU alone, the incidence of AML has been reported to be about 1-3% in two larger studies each encompassing about 100 patients who have been followed over a median of 5 years [1,6]. Two more recent PV studies have documented a much higher incidence of AML after treatment with HU when the patients are followed for longer periods (5.9% at 8.5 years and 8% at 12 years, respectively) [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PV patients treated with HU alone, the incidence of AML has been reported to be about 1-3% in two larger studies each encompassing about 100 patients who have been followed over a median of 5 years [1,6]. Two more recent PV studies have documented a much higher incidence of AML after treatment with HU when the patients are followed for longer periods (5.9% at 8.5 years and 8% at 12 years, respectively) [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with PV who have been treated with HU alone, the risk of transformation is reported to be between 1% [1] and 8% [31]. In patients with ET, the risk of transformation to AL has been reported on average 5% after being treated with HU.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The long median overall survival observed could be related to the low incidence of high-risk thrombosis, reflecting a peculiar effect of this drug on thrombopoiesis as suggested by other authors. 6 The incidence of acute leukemia is lower than that observed after 32P or chlorambucil treatment 1 and not higher than that observed after hydroxyurea treatment: 17,18 therefore, prospective, collaborative and randomized clinical trials are needed to assess the role of these two myelosuppressive drugs on the outcome of PV patients.…”
Section: Figurementioning
confidence: 96%
“…[14][15][16] The results of PVSG Protocol-08 indicated that HU supplemented by occasional phlebotomy was able to decrease the incidence of life-threatening thrombosis when compared with historical phlebotomized patients (13.7 vs 38.1%). In addition, during the first 378 weeks of the study, acute leukemia appeared only in two HU-treated patients (3.9%), leading the authors to conclude that this drug had to be considered the drug of choice, particularly in younger patients previously untreated by myelosuppressive therapy.…”
Section: Figurementioning
confidence: 99%
“…As far as I can derive from the issue in Seminars of Hematology in January 1997 [42], there is no residual activity of the PVSG and all PVSG protocols are closed many years ago [11,43]. We have discussed and learned much from the results of the PVSG studies at the various meetings of the EWG.MPD since 1994 summarized in The Chronic Myeloproliferative Disorders CMPD): Essential Thrombocythemia, Polycythemia Vera and Megakaryocytic Myeloid Metaplasia.…”
Section: Controversies In the Management Of Mpds: What Is The Progresmentioning
confidence: 99%